2014
DOI: 10.1111/avsc.12086
|View full text |Cite
|
Sign up to set email alerts
|

The impact of native large herbivores and fire on the vegetation dynamics in the Cape renosterveld shrublands of South Africa: insights from a six‐yr field experiment

Abstract: Question Renosterveld – a vegetation complex within the Fynbos Biome of South Africa – occurs in multiple structural states, including shrublands and various types of grasslands, lawns and herb‐lands. Uncertainty exists over whether the present unpalatable shrubland state might have replaced a historical grassland state. Settled agriculture characterized by fixed burning cycles and overgrazing by livestock has been blamed for this putative change. However, the disappearance of native large herbivores has also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…Eland dung was found at all six sites whereas bontebok dung was found at all but the last two fynbos sites (sand plain fynbos and limestone fynbos). Previously, Radloff et al 3 noted that bontebok avoid fynbos whereas eland are found throughout fynbos, including limestone fynbos. To reduce chances of pseudoreplication, we sampled only a single pellet of bontebok or eland dung from a dung pile; only dung piles greater than 5 m apart were sampled and, as judged by colour, only relatively fresh samples were collected until a total of 10 pellets had been sampled from within each vegetation type.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eland dung was found at all six sites whereas bontebok dung was found at all but the last two fynbos sites (sand plain fynbos and limestone fynbos). Previously, Radloff et al 3 noted that bontebok avoid fynbos whereas eland are found throughout fynbos, including limestone fynbos. To reduce chances of pseudoreplication, we sampled only a single pellet of bontebok or eland dung from a dung pile; only dung piles greater than 5 m apart were sampled and, as judged by colour, only relatively fresh samples were collected until a total of 10 pellets had been sampled from within each vegetation type.…”
Section: Methodsmentioning
confidence: 99%
“…2,3 The two dominant grassland/ renosterveld grass species at Potberg are Cymbopogon popschilli (Andropogoneae) and Cynodon dactylon (Chloridoideae), 3 to which can be added the relatively widespread Themeda triandra (Andropogoneae). All three species utilise the C4 photosynthetic pathway rather than the C3 pathway.…”
Section: Introductionmentioning
confidence: 99%
“…10 Secondly, a study on natural recovery concluded that vegetation recovery is occurring naturally in mountain renosterveld (Table 2). 4,19 Lastly, studies on restoration benefits have confirmed that restoring abandoned agricultural fields improves hydrological and soil retention services. 20,21 The above three outcomes are an indication that ecological restoration initiatives in renosterveld are yielding mixed results.…”
Section: Seed Bank Of Remnant and Degraded Renosterveldmentioning
confidence: 98%
“…This is possible where grazing and browsing animals are allowed to utilise palatable species, leaving unpalatable species to dominate abandoned agricultural fields. 4 Besides, grazing has also been reported to disperse seeds of invasive alien grasses rather than those of native shrubs. 12 Secondly, natural succession will only be successful where remnants of renosterveld are close to the abandoned agricultural fields so as to allow seed dispersal to take place.…”
Section: Seed Bank Of Remnant and Degraded Renosterveldmentioning
confidence: 99%
See 1 more Smart Citation